Surgical management of a large maxillary non-odontogenic cyst using Le Fort I osteotomy: a short case report - Grzelczyk Lucie; Daurade Mathieu (Journal of Oral Medicine and Oral Surgery)
Introduction: Non-odontogenic epithelial cysts are rare and are typically treated by enucleation. The choice of surgical approach is influenced by factors such as lesion size, location, and patient-specific anatomy. Observation: This case involves a 62-year-old male with a large (33 × 36 mm) maxillary epithelial cyst complicated by a history of cleft palate. A Le Fort I osteotomy was selected due to the lesion's size, posterior location, and the anatomical limitations imposed by the cleft. Alternative approaches, such as cyst decompression, marsupialization, or endoscopy, were considered but ruled out due to the lesion's posterior position and volume. The osteotomy provided optimal access for complete enucleation while minimizing the risk of complications. Conclusion: Despite being more invasive, the Le Fort I osteotomy offered superior visibility and access, ensuring complete removal of the cyst.